2016
DOI: 10.3233/nre-161302
|View full text |Cite
|
Sign up to set email alerts
|

The effects of virtual reality-based bilateral arm training on hemiplegic children’s upper limb motor skills

Abstract: This study confirmed that for children with hemiplegic with cerebral palsy, bilateral arm training based on virtual reality can be an effective intervention method for enhancing the upper limb motor skills on the affected side, as well as bilateral coordination ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
18

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 23 publications
1
35
0
18
Order By: Relevance
“…Chen et al40 found that individuals with CP (hemiplegic) who presented less damage in functionality and a better understanding of the task favored performance improvement, presenting better results after an intervention through VR. In the study by Do et al,41 VR programs were found to be capable of changing motor skills (motor performance) in individuals with hemiplegic CP. Likewise, Pourazar et al42 showed significant improvements in a group of children with CP after an intervention program using VR.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al40 found that individuals with CP (hemiplegic) who presented less damage in functionality and a better understanding of the task favored performance improvement, presenting better results after an intervention through VR. In the study by Do et al,41 VR programs were found to be capable of changing motor skills (motor performance) in individuals with hemiplegic CP. Likewise, Pourazar et al42 showed significant improvements in a group of children with CP after an intervention program using VR.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence for AVG use to improve gross motor skills in children with CP has primarily been reported for Nintendo's Wii and WiiFit, systems in which interaction with the game is via a hand-held controller or a force platform (e.g., Chiu et al, 2014;Do et al, 2016). Full body movement is the medium for game interaction in Microsoft's Xbox360 Kinect motion-capture sensor games.…”
Section: Introductionmentioning
confidence: 99%
“…It can also improve trunk control and concentration [56]. Active participation, receiving feedback and repetition of movements during the VRBT intervention, assists in motor learning that induces cortical reorganisation and neural plasticity changes in the brain [57][58][59]. VRBT also increases the exercise compliance level in achieving selective motor control and enhances the effectiveness of conventional physiotherapy [60].…”
Section: Virtual Reality-based Therapy (Vrbt)mentioning
confidence: 99%